Examining implementation of an intervention to reduce psychological distress and intimate partner violence in a refugee camp setting. Issue 11 (2nd November 2022) - Greene, M. Claire; Scognamiglio, Thea; Likindikoki, Samuel L.; Misinzo, Lusia; Njau, Tasiana; Bonz, Annie; Ventevogel, Peter; Mbwambo, Jessie K. K.; Tol, Wietse A.
ABSTRACT: An integrated approach to reduce intimate partner violence and improve mental health in humanitarian settings requires coordination across health and protection services. We developed and tested the Nguvu intervention, which combined evidence-based interventions for psychological distress and intimate partner violence among Congolese refugee women in Nyarugusu refugee camp (Tanzania). We conducted 29 semi-structured interviews with Nguvu participants and stakeholders to explore the relevance, acceptability, feasibility, and impact of this intervention. Participants reported that the intervention aligned with needs and filled a gap in programming, yet further adaptations may improve the fit of the intervention. The Nguvu intervention was acceptable to participants, including group discussion of sensitive topics. Confidentiality was highly regarded among staff and participants, which improved safety and acceptability. It was feasible to train non-specialist refugee workers to deliver the intervention with adequate supervision. Facilitators noted contextual challenges that made it difficult to implement the intervention: limited infrastructure, competing priorities, and population mobility. The intervention was perceived to improve awareness of the association between violence and mental health, reduce self-blame, and build skills to improve wellbeing. Recommended adaptations reveal promising, yet challenging future directions for addressing social determinants of mental health and implementing multi-sectoral programmes in complex humanitarian settings.